A multicomponent intervention program to Prevent and Reduce AgItation and phySical rEstraint use in the ICU (PRAISE): study protocol for a multicenter, stepped-wedge, cluster randomized controlled trial - Rens W. J. Kooken; Bram Tilburgs; Rob ter Heine; Bart Ramakers; Mark van den Boogaard; on behalf of the PRAISE study group (Trials, 2023)
Abstract Background Physical restraints remain to be commonly used in agitated intensive care unit (ICU) patients worldwide, despite a lack of evidence on efficacy and safety and reports of detrimental short and long-term consequences, such as prolonged delirium and a longer ICU length of stay. Physical restraint minimization approaches have focused mainly on educational strategies and other non-pharmacological interventions. Combining these interventions with goal-directed light sedation therapy if needed may play an important contributory role in further reducing the use of physical restraints. The aim of the study is to determine the effectiveness of a multicomponent intervention (MCI) program, combining person-centered non-pharmacological interventions with goal-directed light sedation, compared to physical restraints. Methods A multicenter stepped-wedge cluster randomized controlled trial will be conducted in six Dutch ICUs. A power calculation based total of 480 (expected to become) agitated adult patients will be included in 26 months with a subsequent 2-year follow-up. Patients included in the control period will receive standard care with the current agitation management protocol including physical restraints. Patients included in the intervention period will be treated with the MCI program, consisting of four components, without physical restraints: education of ICU professionals, identification of patients at risk for agitation, formulation of a multidisciplinary person-centered care plan including non-pharmacological and medical interventions, and protocolized goal-directed light sedation using dexmedetomidine. Primary outcome is the number of days alive and outside of the ICU within 28 days after ICU admission. Secondary outcomes include length of hospital stay; 3-, 12-, and 24-month post-ICU quality of life; physical (fatigue, frailty, new physical problems), mental (anxiety, depression, and post-traumatic stress disorder), and cognitive health; and 1-year cost-effectiveness. A process evaluation will be conducted. Discussion This will be the first multicenter randomized controlled trial determining the effect of a combination of non-pharmacological interventions and light sedation using dexmedetomidine compared to physical restraints in agitated ICU patients. The results of this study, including long-term patient-centered outcomes, will provide relevant insights to aid ICU professionals in the management of agitated patients. Trial registration NCT05783505, registration date 23 March 2023.